Integration of HAS with blockchain as halal sustainability in maqashid sharia perspective - Qanita, Ariza; Maghfuroh, Nuril Laila; Muhammad, Zaydan (Journal of Halal Product and Research (JHPR), 2024)
Efforts to develop the halal industry, especially in the food sector, continue to be encouraged by the government. One of that is by issuing a regulation that requires all circulating products to have a halal certificate. But in fact, not a few business actors commit acts of fraud to obtain the halal certificate. Therefore, what must be considered is not just the labeling of the finished product, but the sustainability of production management and the halal supply chain which can be initiated through the implementation of a Halal Assurance System (HAS) with blockchain management. Halal sustainability has an important role based on the maqashid sharia aspect. This study used a qualitative approach with the type of library research. The data analysis technique used is PESTELE analysis. The results of the study showed that halal sustainability through the application of blockchain-based HAS fulfills the five important elements in maqashid dharuriyyah, namely hifdz al-diin, hifdz al-nafs, hifdz al-'aql, hifdz al-nasl and hifdz al-maal through aspects of embodiment of religious value and consumer protection. PESTELE analysis results showed that an important factor that needs to be considered in the development of the Halal Assurance System is the human error or social and ethical aspects of business actors or those involved in halal production management. This can be the basis for suggestion regarding the importance of increasing education and training in halal management.